PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN - Muamar Khadafi (Jurnal MEBIS (Manajemen dan Bisnis), 2018)
This study focused on the effect that human resource management (HRM) practices have on employee performance. The study sought to establish the effect of training, performance-related pay, employee empowerment, job design and job security on employee performance of industrial sectors in Batam Island. The research design used was descriptive survey research design. The target population was all the industrial sector employees. Purposive sampling technique was used. Data was collected using questionnaires and analyzed using descriptive statistics such as frequencies and percentages. Correlation and regression analysis was done to establish the relationship between various HRM practices and employee performance. Data was presented in form of tables, charts and graphs. Based on the findings, job design has the greatest impact on increasing employees’ level of performance. Employee empowerment has also got an effect of increasing employees’ level of performance. Training and development, job security and pay related performance have got no impact on employee performance.The research results show that job design and employee empowerment have positive significance to raise employee performance.